Analisis Yuridis Perlindungan Hukum terhadap Korban Pemalsuan Akta dan Tanggung Jawab Perdata Serta Pidana Notaris Berdasarkan UUJN dan KUHP Terbaru - Davit Hutajulu; Rudy Hartono; Gracecia Diva Vanessa; Reza Farhansyah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Forgery of authentic deeds is a form of crime that can damage public trust in notarial institutions and cause harm to the community. Legal problems arise when deeds made based on false information or documents give rise to court proceedings and notaries are held accountable. This study aims to analyze legal protection for victims of forged deeds and the civil and criminal liability of notaries based on Law Number 2 of 2014 concerning the Position of Notary and Law Number 1 of 2023 concerning the Criminal Code. The research method used is normative juridical with an approach of regulations, doctrine and court decisions. The results of the study indicate that legal protection for victims is provided through preventive and repressive efforts, either through civil lawsuits, deed cancellation, or criminal sanctions. Notary liability can only be imposed if there is evidence of intent or negligence in the deed-making process.